Transforming and Grappling with Concepts of Activism and Feminism with Indigenous Women Artists - Nagam, Julie (Atlantis, 2008)
This essay reflects on the multiple relations between the socially constructed terms of activism, feminism and Indigenous artists and whether such reflections connect to a larger discussion surrounding colonization, hegemonic western art practices and the lack of female Indigenous artists in the mainstream art world.